Biomimetic Assembly Lines Producing Natural Product Analogs: Strategies from a Versatile Manifold to Skeletally Diverse Scaffolds. Issue 2 (1st February 2016) - Oguri, Hiroki
Abstract: Biosynthetic assembly lines have evolved in nature, adopting divergent processes to produce a vast number of secondary metabolites. Inspired by these biogenetic processes, this account introduces recent investigations by my research group to formulate a synthetic strategy for establishing a biomimetic assembly line. With the aim not only to construct natural product‐relevant scaffolds within 5–7 steps, but also to systematically diversify skeletal and stereochemical properties and functional groups, divergent synthetic processes exploiting a versatile manifold have been developed. This approach allows for cost‐effective production of skeletally diverse and biologically active natural product analogs inaccessible by other means. Discovery of several lead candidates for a neglected tropical disease is a proof‐of‐concept of this synthetic approach. Abstract : Biomimetic assembly lines gaining concise and programmable access to skeletally and stereochemically diverse natural product analogs have been developed. This account illustrates synthetic strategies exploiting versatile manifolds that allow modular assembly of building blocks and subsequent divergent cyclizations to produce densely functionalized scaffolds bearing three‐dimensional structural variations and biological relevance. Successful discovery of several lead candidates for chemotherapy of African sleeping sickness provides the proof‐of‐concept of this synthetic approach.